An Analysis of Heterogeneous Traffic Dominated by Motorcycles at Signalized Intersections in Pekanbaru: Penelitian - Abdul Kudus Zaini; Andika Ronaldo Arman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Pekanbaru City, one of Indonesia’s growing metropolitan areas, faces significant traffic challenges, particularly due to the increasing number of motorcycles. As the population rapidly expands, the volume of motorized vehicles rises, leading to frequent congestion—especially during peak hours. This study analyzes traffic performance at signalized intersections in Pekanbaru, focusing on congestion problems resulting from motorcycle dominance. The research examines vehicle volume, queue lengths, and delays at selected intersections. Findings reveal that the Gramedia (Nangka) and Governor’s Office intersections experience high traffic density, which elevates the risk of accidents. This study offers practical recommendations to support traffic management decisions and guide the development of a more efficient urban transportation system.